How the Skate Embryo Develops: A Fine Developmental Timeline of Kong Skate Okamejei kenojei (Müller & Henle, 1841) - Guang, Gao; Zhizhong, Xiao; Yuting, Ma; Xiao, Chen; Yongshuang, Xiao; Jun, Li (Frontiers in Marine Science, 2022)
Cartilaginous fishes, as an important group of jawed vertebrates, hold great promise for improving our understanding of vertebrate evolution. Previous studies have established a good staging scheme for shark embryos. However, to date, little attention has been paid to the development of skate embryos. In this study, we established a fine developmental timeline for the Kong skate. We hatched eggs of the Kong skate (Okamejei kenojei) at fixed temperatures (16.5 °C ± 0.5 °C) while observing three samples every day and recorded the complete embryonic development. The embryo weight and development time were found to have a quadratic relationship. The weight-at-day curve was fitted by y = 0.0005x2 - 0.0109x + 0.0882 (R² = 0.9406). In addition, complete embryonic development from gastrula to skate larvae took 92 ± 5 days. Here, we divided the entire development process into 39 stages. This shows that the jaw of O. kenojei is developed from the first pair of pharyngeal arches, and its body disc is formed by the fusion of the pectoral fin and head. The eyespots began to form from stage 36 and then became thicker and bigger until the young skate broke out of the egg. Notably, we found that males and females develop differently from stage 31; the end of the male pelvic fins expands inward, which develop into copulatory organ-claspers, whereas in the females, they do not expand. To the best of our knowledge, this is the first study to record the embryonic development of eyes, body discs, eyespots, and other organs of O. kenojei in detail. We hope that our work will provide valuable information for researchers to identify specific time points for developing skate embryos.